Cell-based and antibody-mediated immunotherapies directed against leukemic stem cells in acute myeloid leukemia: Perspectives and open issues. (13th July 2020) - Valent, Peter; Bauer, Karin; Sadovnik, Irina; Smiljkovic, Dubravka; Ivanov, Daniel; Herrmann, Harald; Filik, Yüksel; Eisenwort, Gregor; Sperr, Wolfgang R.; Rabitsch, Werner
Abstract: Despite new insights in molecular features of leukemic cells and the availability of novel treatment approaches and drugs, acute myeloid leukemia (AML) remains a major clinical challenge. In fact, many patients with AML relapse after standard therapy and eventually die from progressive disease. The basic concept of leukemic stem cells (LSC) has been coined with the goal to decipher clonal architectures in various leukemia-models and to develop curative drug therapies by eliminating LSC. Indeed, during the past few years, various immunotherapies have been tested in AML, and several of these therapies follow the strategy to eliminate relevant leukemic subclones by introducing LSC-targeting antibodies or LSC-targeting immune cells. These therapies include, among others, new generations of LSC-eliminating antibody-constructs, checkpoint-targeting antibodies, bi-specific antibodies, and CAR-T or CAR-NK cell-based strategies. However, responses are often limited and/or transient which may be due to LSC resistance. Indeed, AML LSC exhibit multiple forms of resistance against various drugs and immunotherapies. An additional problems are treatment-induced myelotoxicity and other side effects. The current article provides a short overview of immunological targets expressed on LSC in AML. Moreover, cell-based therapies and immunotherapies tested in AML are discussed. Finally, the article provides an overview about LSC resistance and strategies to overcome resistance. : Abstract : Expression of cell surface target antigens on leukemic stem cells (LSC) in acute myeloid leukemia (AML) (left image) and on normal hematopoietic stem cells (right panel). Most of the clinically relevant surface target antigens are not only expressed on AML LSC but also in normal stem cells. In several instances, expression levels are higher on AML LSC than on normal stem cells providing a (small) therapeutic window. Only a few potential surface targets, such as CLL1 (CD371), are selectively (aberrantly) expressed on AML LSC but not on normal stem cells.